Analisis Kualitas Website Startup Kerupuka3.Com Menggunakan Metode Webqual - Ardiansyah, Reza; titah; Alisyahbana, Takdir; sutabri, tata (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
A3 Palembang crackers is an online marketplace that provides a variety of delicious, halal, and can be sent throughout Indonesia. Available in various packaging sizes, A3 crackers have been enjoyed by customers throughout Indonesia . This will certainly be a concern for managers of A3 crackers to fix and evaluate the quality of service on their website. Because the quality of this service is the key measure of customer satisfaction. The purpose of this study is to analyze the quality of the A3 cracker website using the Webqual method, the Webqual method is an instrument to assess the usefulness, information, and quality of service interactions from the website. Webqual is also one of the methods or techniques for measuring website quality based on user perception The results of the calculation of Usability, Information Quality, Interaction Quality, Overall Imppression, and correlation analysis are valued at 126, 123, 117, 123 thus the quality of the website falls into the good category. And the contribution of the interaction quality dimension value to the overall website quality is 0.561 with a moderate relationship level because it is on a scale of 0.40 – 0.599.